RANCANG BANGUN MEDIA PERMAINAN MONOPOLI EDUKATIF“MERKAYASA” UNTUK MENANAMKAN KARAKTER TOLERANSI DALAM PEMBELAJARAN IPS - Cindy Kusuma Putri; Umar Umar; Muh. Husen Arifin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research is motivated by the lack of interesting and fun learning media in carrying out the learning process and inculcating the value of the character of tolerance to students. The use of fun learning media is currently very much needed as an effort to overcome student boredom with conventional methods carried out by teachers during the learning process, especially in social studies learning in elementary grade IV. The purpose of this study is to produce learning media in the form of the educational monopoly game "MERKAYASA" to instill the character of tolerance in social studies learning in Grade IV Elementary Schools. The method used in this research is the Design and Development (D&D) method using research procedures in the form of the ADDIE model, which consists of five stages (Analysis, Design, Development, Implementation, Evaluation). The participants involved in this study were material expert validators, media expert validators, teachers and seven fourth grade students at SDN 3 Kenanga Sumber District. The results of the feasibility test from the material expert validator are 87.5% with the "Very Eligible" category, from the media expert validator 92.3% with the "Very Eligible" category. Then, the score obtained from the teacher's response questionnaire is 94.2% with the "Very Eligible" category, and the score obtained from the student response questionnaire is 92.5% in the "Very Eligible" category. Based on the results obtained, it can be concluded that the educational monopoly game media "MERKAYASA" is very suitable to be used in helping the learning process.